The hermitage of the Golden Forest in Rytwiany – as a monument of history - Brykowska Maria (Protection of Cultural Heritage, 2019)
: The recognition of the Congregation of the Camaldolese Hermits Monte Corona monastery in Rytwiany as a Monument of History in 2018 was fully justified. Built from the funds of Tęczyński Foundation (1617-1637) and finished by the Opaliński family, the hermitage is distinguished by its Italian program, composition, architecture and baroque decoration and furnishings of the church. Since 1819, the condition of the monastery’s buildings deteriorated despite conservation works. The process was halted by revalorization, adaptation of the hermitage to its contemporary function and conservation works, organized since 2001 by Rector W. Kowalewski. In 2008, the Relaxation and Contemplation Therapy Centre SpeS was opened, while preserving the sacrum of the church and the Camaldolese tradition. Today, the hermitage has a religious, cultural and social function. The authentic values of the monument have been preserved. It organises visits to the church, the Museum and the Camaldolese Gallery, church ceremonies for pilgrims, and open-air events, symposiums and stays for guests (gardens, high standard hotel and restaurant, sauna). The monument and contemporary attractions are promoted on the Internet, in their own publications and folders.